Extra-cellular matrix rigidity may dictate the fate of injury outcome. (21st May 2019) - Peurichard, D.; Ousset, M.; Paupert, J.; Aymard, B.; Lorsignol, A.; Casteilla, L.; Degond, P.
Highlights: A two-dimensional individual based model is developed for adipose tissue reconstruction after injury. The same mechanisms for adipose tissue morphogenesis could be at play in tissue reconstruction after injury. The fate of injury outcome could mainly be driven by the properties of the reconstructed ECM and the mechanical forces induced by it. Abstract: After injury, while regeneration can be observed in hydra, planaria and some vertebrates, regeneration is rare in mammals and particularly in humans. In this paper, we investigate the mechanisms by which biological tissues recover after injury. We explore this question on adipose tissue, using the mathematical framework recently developed in Peurichard et al., J. Theoret. Biol. 429 (2017), pp. 61–81. Our assumption is that simple mechanical cues between the Extra-Cellular Matrix (ECM) and differentiated cells can explain adipose tissue morphogenesis and that regeneration requires after injury the same mechanisms. We validate this hypothesis by means of a two-dimensional Individual Based Model (IBM) of interacting adipocytes and ECM fiber elements. The model successfully generates regeneration or scar formation as functions of few key parameters, and seems to indicate that the fate of injury outcome could be mainly due to ECM rigidity.